Metodyczne aspekty rachunku kosztów w rolnictwie - Kondraszuk, Tomasz (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2010)
Article presents cost account applicability in the agricultural companies regarding to the general theory of economic and organisation of enterprises. The main focus was laid down to analyse of the unit total cost account with variable costs and their applicability in three spheres: requirements of planning and decision making processes, stock valuation and profit, controlling. It was concluded that cost calculation at the level of agricultural enterprise should be an inherent element of integrated information system at the level of registry, planning, decision making and control.